Political support in a frustrated America - Farnsworth, Stephen J., 1961- (Praeger, 2003)
Public confidence and trust in government is low these days. Farnsworth pinpoints this disappointment to shifting expectations of what, exactly, government should do. Politicians were once expected to maintain economic growth, but in our post-scarcity era most citizens expect them to provide services - such as welfare or environmental -that are often contentious. Enlarging the scope of local political empowerment will increase public support by making politics more approachable and responsive.